The Histone Acetyltransferase HpGCN5 Involved in the Regulation of Abiotic Stress Responses and Astaxanthin Accumulation in Haematococcus pluvialis - Huang, Danqiong; Liu, Wenfu; Hu, Qunju; Li, Hui; Wang, Chaogang (Frontiers in Plant Science, 2022)
The histone acetyltransferases (HATs), together with histone deacetylases, regulate the gene transcription related to various biological processes including stress responses in eukaryotes. The present study found a member of HATs (HpGCN5) from a transcriptome of the economic important microalgae Haematococcus pluvialis. Its expression pattern responding to multiple abiotic stresses and its correlation with transcription factors and genes involving in triacylglycerols and astaxanthin biosynthesis under stress conditions were evaluated, aiming to discover its potential biological function. The isolated HpGCN5 was 1712 bp in length encoding 415 amino acids. The signature domains of Acetyltransf_1 and BROMO were presented, as the GCN5 gene from Arabidopsis and Saccharomyces cerevisiae, confirming that HpGCN5 belonging to the GCN5 subfamily of GNAT superfamily. The phylogenetic analysis revealed that HpGCN5 is grouped with GNAT genes from algae and is more close to that from higher plants, compared with yeast, animal, fungus, and bacteria. It was predicted that HpGCN5 is composed of 10 exons and contains multiple stress-related cis-elements in the promoter region, revealing its potential role in stress regulation. Real time quantitative PCR revealed HpGCN5 responds to high light and high salt stresses in a similar behavior, revealed by their down-regulation exposing to stresses. Differently, HpGCN5 expression was significantly induced by SA and Nitrogen-depletion stresses at the early stage, but was drop back after then. The correlation network analysis suggested that HpGCN5 has strong correlation with major genes and a transcription factor involved in astaxanthin biosynthesis. Besides, the correlation was only found between HpGCN5 and few genes involved in triacylglycerols biosynthesis. Therefore, this study proposed that HpGCN5 might play a role in the regulation of astaxanthin biosynthesis. Results in this study firstly examined the role of HATs in stress regulation and will enrich our understanding of the role of HATs in microalgae.